EFFECT OF MANAGEMENT COMMITMENT TO INTERNAL MARKETING ON EMPLOYEES’ SATISFACTION. A CASE STUDY: IMAM JAFAR SADEGH HOSPITAL NURSES - Ali Morovati Sharifabadi; Shima Shahhosseini Bideh (Asian Academy of Management Journal, 2016)
Nowadays, healthcare is an extraordinarily people-centric industry and employees play important roles in the product/service exchange. Internal marketing (IM) forces the employee to treat more hospitably facing customers. The present study examines the effect of management commitment to internal marketing (MCIM) on employees' satisfaction through IM practices. Data were collected from 110 nurses of Imam Jafar Sadegh hospital. The results of structural equation modeling showed the significant effect of MCIM on IM practices (formal internal marketing, informal internal marketing and responsiveness). But verse to what was assumed, there was no significant relation between IM and employees' satisfaction.